Active control of multifrequency helicopter vibrations using discrete model predictive sliding mode control. (March 2016) - Lu, Yang; Ma, Xunjun
Conventional control laws are limited predominantly to control the rotor main passing frequency component of helicopter structural response, while the remaining frequency components still make harsh vibration. The primary objective of this paper is to develop a novel hybrid controller to control multifrequency helicopter vibrations. The architecture of the feedforward–feedback hybrid control law is first proposed based on the filtered-x least mean square algorithm. Subsequently, the feedback loop called discrete model predictive sliding mode controller is designed in detail which combines discrete sliding mode control and model predictive control. Discrete sliding mode control is employed for its robustness, while the chattering phenomenon is eliminated and then the system state is steered to reach the sliding surface precisely in an optimal manner with the assistance of model predictive control. Also, the stability, robustness, and state tracking error bound of the feedback controller are analyzed. Performance enhancement of the hybrid control law is verified by simulations based on a simplified helicopter finite element model. By comparison with the multifrequency filtered-x least mean square algorithm under various cases, the results clearly demonstrate that the proposed algorithm deals with the rotor main passing frequency component and its harmonics simultaneously with faster convergence and better stability.